Extreme Weather - John Sallis, Philip (IntechOpen, 2018)
The term extreme weather normally conjures up thoughts of massive storms or heat waves or overtly cold temperatures. These are all examples of what we might consider as weather events that occur out of the ordinary or what is regarded as the normal pattern of calm, heat, cold, dry, or wet conditions for one season of the year or another. The point is that if we consider an oscillation of data points in a weather pattern and plot a mean through it, extreme weather can be observed as a perturbation in a distribution of climatic events over time. These events may be short-lived, such as a wind gust occurrence, or of longer duration, such as heavy rain leading to flooding. Importantly, once initiated, a perturbation event has an associated consequence, which usually requires human intervention to rectify the event's consequences.